(untitled) (Eurasian Journal of Humanities and Social Sciences, 2025)
The Nigerian aviation sector, which is a core element of transport and economy of the country, has faced numerous strategic inflection points, which disrupt its business models. Such points of inflection, which are fueled by technological innovations, regulatory reform and altered consumer expectations, presents the need to have a complete reconsideration of conventional business approaches. In this study the researcher looks at how the Nigerian airlines redeveloping their business is confronting these challenges. The paper illustrates how innovation, online connectivity, and partners can help in the redesigning of a business model, in the case studies provided by the analysis of Ibom Air, Air Peace and Arik Air. Findings show the need to continuously learn in order to adapt and gain a competitive advantage and long term sustainability. More so, the research provides policy inputs that can guide the various stakeholders in the aviation industry to navigate the change